Lithiated porous silicon nanowires stimulate periodontal regeneration - Kaasalainen, Martti; Zhang, Ran; Vashisth, Priya; Birjandi, Anahid Ahmadi; S'Ari, Mark; Martella, Davide Alessandro; Isaacs, Mark; Mäkilä, Ermei; Wang, Cong; Moldenhauer, Evelin; Clarke, Paul; Pinna, Alessandra; et al. (Nature communications, 2024)
Periodontal disease is a significant burden for oral health, causing progressive and irreversible damage to the support structure of the tooth. This complex structure, the periodontium, is composed of interconnected soft and mineralised tissues, posing a challenge for regenerative approaches. Materials combining silicon and lithium are widely studied in periodontal regeneration, as they stimulate bone repair via silicic acid release while providing regenerative stimuli through lithium activation of the Wnt/β-catenin pathway. Yet, existing materials for combined lithium and silicon release have limited control over ion release amounts and kinetics. Porous silicon can provide controlled silicic acid release, inducing osteogenesis to support bone regeneration. Prelithiation, a strategy developed for battery technology, can introduce large, controllable amounts of lithium within porous silicon, but yields a highly reactive material, unsuitable for biomedicine. This work debuts a strategy to lithiate porous silicon nanowires (LipSiNs) which generates a biocompatible and bioresorbable material. LipSiNs incorporate lithium to between 1% and 40% of silicon content, releasing lithium and silicic acid in a tailorable fashion from days to weeks. LipSiNs combine osteogenic, cementogenic and Wnt/β-catenin stimuli to regenerate bone, cementum and periodontal ligament fibres in a murine periodontal defect.
Keywords: křemík; poréznost; Animals; nanodráty; beta-katenin; Silicon; Porosity; Lithium; Silicic Acid; zvířata; Nanowires; zubní cement (tkáň); Mice; Dental Cementum; beta Catenin; kyselina křemičitá; lithium; myši